A Study on Patient Behaviors Towards Dental Visits and Oral Health during COVID-19 Outbreak - Marriam Mahmood (University Library System, University of Pittsburgh, 2022)
Background               Investigating the impact of COVID-19 pandemic on oral health and patient attitudes towards a dental visit is essential to improving access to oral health care during the pandemic. This calls for studying the chief patient fears, preferences and future intentions related to dental visits during the COVID-19 pandemic. Methods A web-based survey was administered to the public within the US in December 2020. The participants (N=502) answered questions about their oral health, trust level for dental offices, chief concerns and preferences related to dental visits during the COVID-19 outbreak. We used descriptive statistics (e.g., Chi-square, Shapiro-Wilk, Kruskall-Wallis and Wilcoxon Signed Rank tests) to find if demographics, oral health history or social behaviors were associated with the relevant patient attitudes.    Results When queried about COVID-19's impact on oral health, 62.5% respondents reported a minimal impact, 7.2% a positive impact, and 30.3% a negative impact. There were statistically significant differences in responses based on respondents' ethnicity (N=502, P=.033) and dental visit history during the pandemic (N=502, P=.008). The public trust rating for COVID-19-related precautions was more favorable towards the medical offices than the dental offices (N=502, P<.001). The majority considered contracting COVID-19 from the other patients in the dental office waiting area (60.4%), the dentist/hygienist/dental assistants (54.2%), and the aerosols (50.8%) as their chief concerns. 20.1% respondents preferred no other patient, 25.1% only one more patient, and 31.1% up to three more patients in the waiting area during a dental visit. Conclusions The reported impact of COVID-19 on self-perceived oral health was modest for most respondents. Patients' chief concerns for a dental visit include contracting COVID-19 infection from other patients, dentists, and aerosols in the operatory. It may be beneficial if dental practices avoid scheduling multiple patients in the waiting area to improve access to oral health care.